Hemodynamic and Pulmonary Permeability Characterization of Hantavirus Cardiopulmonary Syndrome by Transpulmonary Thermodilution - LOPEZ HERNANDEZ, RENE RAMON; Rodrigo Pérez-Araos; Álvaro Salazar; Ana L. Ulloa; VIAL COX, MARIA CECILIA; VIAL CLARO, PABLO AGUSTIN; GRAF SANTOS, JERÓNIMO (My University, 2019)
Hantavirus cardiopulmonary syndrome (HCPS) is characterized by capillary leak, pulmonary edema (PE), and shock, which leads to death in up to 40% of patients. Treatment is supportive, including mechanical ventilation (MV) and extracorporeal membrane oxygenation (ECMO). Hemodynamic monitoring is critical to titrate therapy and to decide ECMO support. Transpulmonary thermodilution (TPTD) provides hemodynamic and PE data that have not been systematically used to understand HCPS pathophysiology. We identified 11 HCPS patients monitored with TPTD: eight on MV, three required ECMO. We analyzed 133 measurements to describe the hemodynamic pattern and its association with PE. The main findings were reduced stroke volume, global ejection fraction (GEF), and preload parameters associated with increased extravascular lung water and pulmonary vascular permeability compatible with hypovolemia, myocardial dysfunction, and increased permeability PE. Lung water correlated positively with heart rate (HR, r = 0.20) and negatively with mean arterial pressure (r = −0.27) and GEF (r = −0.36), suggesting that PE is linked to hemodynamic impairment. Pulmonary vascular permeability correlated positively with HR (r = 0.31) and negatively with cardiac index (r = −0.49), end-diastolic volume (r = −0.48), and GEF (r = −0.40), suggesting that capillary leak contributes to hypovolemia and systolic dysfunction. In conclusion, TPTD data suggest that in HCPS patients, increased permeability leads to PE, hypovolemia, and circulatory impairment.
Keywords: hantavirus cardiopulmonary syndrome; hantavirus pulmonary syndrome; transpulmonary thermodilution; pulmonary edema; andes virus; adolescent; adult; capillary permeability; female; hantavirus; hantavirus infections; hemodynamics; humans; lung; male; middle aged; permeability; pulmonary edema; retrospective studies; stroke volume; thermodilution; young adult; adolescent; adult; article; artificial ventilation; blood vessel permeability; cardiopulmonary hemodynamics; cerebrovascular accident; clinical article; cohort analysis; enzyme linked immunosorbent assay; female; hantavirus cardiopulmonary syndrome; hantavirus pulmonary syndrome; heart ejection fraction; heart left ventricle enddiastolic volume; heart muscle contractility; heart rate; human; hypovolemia; lung extravascular fluid; male; mean arterial pressure; myocardial disease; nonhuman; observational study; pathophysiology; prospective study; real time polymerase chain reaction; retrospective study; reverse transcription polymerase chain reaction; thermodilution; capillary permeability; hantavirus; hantavirus infection; heart stroke volume; hemodynamics; lung; lung edema; middle aged; pathophysiology; permeability; procedures; thermodilution; young adult